Application of Nanoliposome Alprostadil in the Perioperative Period of Percutaneous Coronary Intervention to Reduce In-Stent Restenosis: A Systematic Review and Meta-Analysis - Decai Zhu; Dawei Wang; Zhen Zhao; Qingqing Liu; Rongyuan Yang; Qing Liu (Journal of Interventional Cardiology)
Background. In-stent restenosis (ISR) is a common complication after percutaneous coronary intervention (PCI) surgery for patients with coronary atherosclerotic heart disease (CHD). Reports indicate alprostadil may reduce ISR, and this study aimed at reviewing and summarizing the effect of nanoliposome alprostadil on ISR by meta-analysis. Methods. Articles were searched from databases, and meta-analysis was performed in Review Manager software. Funnel plots were performed to evaluate the publication bias, and sensitivity analysis was performed to determine the robustness of the overall treatment effects. Results. Initially, 113 articles were identified, and 5 studies of 463 subjects were included for analysis eventually. The primary endpoint, i.e., the occurrence of ISR after PCI, occurred in 11.91% of the alprostadil treatment group (28 from 235 patients) vs. 21.49% of the conventional treatment group (49 from 228 patients) and showed a statistical significance in our pooled data (χ2 = 7.654, P=0.006), while there was no statistically significant difference in all of the separate studies. We observed no statistical methodological heterogeneity among the studies (P=0.64, I2 ≈ 0%). The pooled odds ratio (OR) of the occurrence of ISR was 49% in a fixed-effect model, and the 95% confidence boundary (95% CI) was 29% to 81%. The funnel plot did not show serious publication bias, and sensitivity analysis showed well robustness of the overall treatment effect. Discussion. In conclusion, the early application of nanoliposome alprostadil after PCI could effectively reduce the occurrence of ISR, and the overall effect of alprostadil treatment in reducing ISR after PCI was relatively stable.